ASPEK KEKERASAN SEBAGAI REFLEKSI DAN FORMATIF KONDISI SOSIAL POLITIK DI EKS-TIMOR TIMUR DALAM JAZZ PARFUM & INSIDEN KARYA SENO GUMIRA AJIDARMA - Nurhadi, Nurhadi (LITERA, 2016)
This study aims to describe (1) aspects of violence in short stories in Jazz, Parfum, dan Insiden, (2) socio-political conditions as backgrounds to the violence, (3) the possibility for the fiction to reform society. The data source was Jazz, Parfum, dan Insiden by Seno Gumira Ajidarma. The data were analyzed by the content analysis employing the descriptive qualitative technique. The data trustworthiness was assessed through the semantic validity. The findings show that (1) aspects of violence include murder, torture, kidnap, rape, and other types of violence, (2) socio-political conditions as backgrounds to the violence are human right violations including the Dili incident at the Santa Cruz cemetery on 12 November 1991 and the conditions of the occupied East Timor in general, and (3) the fiction has a role in forming readers' awareness of violent acts by government apparatus in the occupation of East Timor by the New Order government that tended to be militaristic and authoritarian. The fiction indirectly gave contribution to the downfall of the New Order government and the independence of Timor Leste. Keywords: violence, East Timor, literature's reflective role, literature's formative role